2014
DOI: 10.1016/j.pain.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of satisfaction with pain treatment in the acute postoperative period: Results from the international PAIN OUT registry

Abstract: Patient ratings of satisfaction with their postoperative pain treatment tend to be high even in those with substantial pain. Determinants are poorly understood and have not previously been studied in large-scale, international datasets. PAIN OUT, a European Union-funded acute pain registry and research project, collects patient-reported outcome data on postoperative day 1 using the self-reported International Pain Outcome Questionnaire (IPO), and patient, clinical, and treatment characteristics. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
82
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 27 publications
11
82
0
7
Order By: Relevance
“…Interestingly, this was the only PRO that yielded a clinically relevant effect size in the current study, indicating perhaps, the increasing role of patient participation in health care. In a recent publication assessing a cohort of patients from PAIN OUT, participation in decisions about treatment was one of the three PROs, along with degree of relief received and no desire to receive more treatment, which strongly influenced satisfaction with pain treatment (Schwenkglenks et al, 2014). PROs in pain studies have highly skewed, nonnormal distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this was the only PRO that yielded a clinically relevant effect size in the current study, indicating perhaps, the increasing role of patient participation in health care. In a recent publication assessing a cohort of patients from PAIN OUT, participation in decisions about treatment was one of the three PROs, along with degree of relief received and no desire to receive more treatment, which strongly influenced satisfaction with pain treatment (Schwenkglenks et al, 2014). PROs in pain studies have highly skewed, nonnormal distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pain experience may be different from that in our patients (Girard-Tremblay, et al, 2014). Another report indicated that the most severe pain experience was 2 hours after surgery (Schwenkglenks, et al, 2014), and the last pain evaluation time (4 hours after surgery) may be too short to discriminate the effects of different doses of propacetamol. In the present study, the time to request rescue analgesic was about 80 minutes after surgery, which was in accordance with results from the previous study (2 hours).…”
Section: Discussionmentioning
confidence: 66%
“…In this respect, it is important to characterize the pain experience in all its domains, to assess the impact of pain on organic, emotional and behavioral functioning of the individual, to identify factors that contribute to the maintenance or exacerbation of pain, to select treatment alternatives, and to verify the effectiveness of the therapies employed. Systematically conducted and recorded assessments, which use specific scales to characterize and measure the pain condition, may contribute to improve the management of the painful experience 9 . Laparoscopy was introduced in 1987 and has since then been used for multiple intraabdominal procedures because of the reduced patient discomfort, shorter hospitalization time and early return to work 10 .…”
Section: ■ Discussionmentioning
confidence: 99%